Analisis Determinasi Kualitas Audit Oleh Aparat Pengawasan Intern Pemerintah (APIP) Kabupaten Batanghari - zulkipli, zulkipli; Simanjuntak , Pranatalindo (Jurnal Akuntansi & Keuangan Unja, 2024)
This study entitled "Analyze The Factors That Determine The Quality Of Audits By Government Internal Audit Apparatus (APIP) In Batanghari Regency”. Audit quality is very important in ensuring accountability and transparency in local government financial management. This research uses a quantitative approach with multiple linear regression analysis tools with SPSS Software 25.0 to examine the relationship between independence, integrity, competence and work experience which influence audit quality. The research population is employees who work at the Batanghari Regency Inspectorate Office. The sample in this study was 32 employees who worked at the Batanghari Regency Inspectorate Office. The sampling technique is a saturated sample/census. The type of data used is primary data through distributing questionnaires. The research results show that partially independence, integrity, competence and work experience influence audit quality at the Batanghari Regency Inspectorate Office.